Layanan Bimbingan Konseling Kelompok dalam Meningkatkan Minat Membaca Siswa - Anggerawati, Nuke Ladyna; Durri, Salma Kaukabud (Program Studi Bimbingan dan Konseling Islam, 2022)
According to UNESCO data, the reading interest of the Indonesian people is very concerning, only 0.001%. This means that out of 1,000 Indonesians, only 1 person is an avid reader. This research method is a qualitative descriptive research type, and uses data collection techniques through observation, interviews and documentation. Before carrying out counseling guidance groups of students have a low interest in reading. From the results of group counseling guidance that has been implemented, it can be concluded that interest in reading can be increased if there is a supportive environment and adequate facilities to change the behavior of interest in reading, especially for elementary school children where children will prefer to form a play group while learning together.